2019
DOI: 10.1038/s41598-019-47876-0
|View full text |Cite
|
Sign up to set email alerts
|

Model based development of tacrolimus dosing algorithm considering CYP3A5 genotypes and mycophenolate mofetil drug interaction in stable kidney transplant recipients

Abstract: This study quantifies the interaction between tacrolimus (TAC) and mycophenolate mofetil (MMF) in kidney transplant recipients. Concentrations of TAC, mycophenolic acid (MPA), and metabolites were analyzed and relevant genotypes were determined from 32 patients. A population model was developed to estimate the effect of interaction. Concentrations of TAC were simulated in clinical scenarios and dose-adjusted trough concentrations per dose (C/D) were compared. Effect of interaction was described as the inverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Hence, C57BL/6 Ubi-GFP recipients were treated daily with vehicle only (mock group) or 1mg/kg tacrolimus (T1 group) from day 0 to day 28 post-HTT (Figure 2a). Tacrolimus whole blood concentrations were measured using a liquid chromatography-mass spectrometry (LC-MS) assay at 3 hours post-dose (C3) (Figure 2b), and showed drug levels similar to those found in transplanted patients [21,22]. After 28 days, histological quantification of epithelial loss and lumen occlusion revealed a significant although heterogeneous effect of tacrolimus in reducing both parameters (Figure 2c-d).…”
Section: Tacrolimus Treatment Reduces Post-transplant Obliterative Lesions and Allows The Survival Of Donor-derived Myofibroblasts In Thementioning
confidence: 65%
“…Hence, C57BL/6 Ubi-GFP recipients were treated daily with vehicle only (mock group) or 1mg/kg tacrolimus (T1 group) from day 0 to day 28 post-HTT (Figure 2a). Tacrolimus whole blood concentrations were measured using a liquid chromatography-mass spectrometry (LC-MS) assay at 3 hours post-dose (C3) (Figure 2b), and showed drug levels similar to those found in transplanted patients [21,22]. After 28 days, histological quantification of epithelial loss and lumen occlusion revealed a significant although heterogeneous effect of tacrolimus in reducing both parameters (Figure 2c-d).…”
Section: Tacrolimus Treatment Reduces Post-transplant Obliterative Lesions and Allows The Survival Of Donor-derived Myofibroblasts In Thementioning
confidence: 65%
“…363,366,367,399 One population pharmacokinetic study did report lower MPA clearance in SLCO1B1 c.388A.G variant (SLCO1B1*1B; rs2306283, p.Asn130Asp) carriers, 377 whereas 2 others reported no effect from any of the SLCO1B1 variants c.388A.G, SLCO1B1*5 (rs4149056, c.521T.C, p.Val174Ala), SLCO1B1*15 (rs2306283, c.388A.G, p.Asn130Asp/rs4149056, c.521T.C, pVal174Ala), (rs2291073, c.226+89T.G), (rs2291075, c.597C.T, p.Phe199=), (rs2417955, 1883T.A, intronic), (rs3829306, c.-61-2168C.T), (rs4149026, 10169A.C, intronic), or (rs4149058, c.727+1260A.G) on MPA PK. 383,395 In another study, SLCO1B1*15 (rs2306283/ rs4149056) carriers displayed lower MPAG concentrations than noncarriers. 400 Regarding SLCO1B3, 2 studies reported reduced MPA exposure in SLCO1B3 c.334 G (rs4149117) carriers as compared to noncarriers, 363,381 whereas 2 other studies found no associations between SLCO1B3 variants and MPA PK.…”
Section: Pg-pk Relationshipsmentioning
confidence: 94%
“…Similarly, one population pharmacokinetic study in 65 KTR reported ABCC2 variants to affect MPA absorption and clearance, 392 whereas others found no associations between ABCC2 variants and MPA PK. [368][369][370]377,383,384,[393][394][395][396] Of note, the interpretation of associative studies on ABCC2 variants and MPA PK may be complicated in patients receiving concomitant immunosuppressive therapy with cyclosporine A, which is not uncommon in the population receiving MPA. Cyclosporine A exhibits extensive inhibition of ABCC2, which likely masks any impact of ABCC2 variants on MPA PK.…”
Section: Pg-pk Relationshipsmentioning
confidence: 99%
“…The research shows that low tacrolimus dosing that does not correspond to the therapeutic range is associated with an increased risk of organ rejection [20] As the concentration of tacrolimus is closely related to graft survival [30,31], it is important to understand the relevant factors, including concomitant drug administration, which influence the variability of tacrolimus and to quantify their effects on the concentration of tacrolimus to assist in drug dosage decisions in patients [32]. M.A.…”
Section: Discussionmentioning
confidence: 99%